Прага в мировосприятии Марины Цветаевой - Грицак, Наталья Руслановна; Hrytsak, N. (Східноєвропейський національний університет імені Лесі Українки, 2013)
В статье охарактеризован чешский период в творчестве поэта начала ХХ века Марины Ивановны Цветаевой. Рассматривается история пребывания русского поэта в эмиграции, анализируется политическая, культурная и литературная жизнь тех лет, позволяющая проследить воплощение жизненных событий в творческом наследии М. Цветаевой. На примере стихотворений «Прага», «Пражский рыцарь» выделены ключевые аспекты образа Праги в мировосприятии М. Цветаевой, в частности показано, что поэт создает образ рыцаря-защитника, стерегущего «реку – дней».The article deals with creative activity of the Czech period at the beginning of the XX century. The emigration period of the Russian writer’s life is considered in the work. The political, cultural and literary life of the defined years which helps to learn the realization of the poet’s reception of the world with further representation in her poetry is analyzed in this article. The key aspects of the image of Prague, based on the poems «Prague» and «Prague Knight» especially on the image of knight-defender are characterized.
The Image of Prague in the Reception of Maryna Tsvitaeva
Keywords: Прага; творческие контакты; поэзия; поэт; индивидуально-авторский стиль; образ; город; Prague; creative contacts; poetry; poet; an individual writing style; image; city